Defaunation is known to have pervasive, negative effects on tropical forests, but this is not the whole story - Gust Boiten; Steffi Dekegel; Nikki Tagg; Jacob Willie (PLoS ONE, 2023)
Ecosystem functioning and integrity are affected by the loss of large-bodied animals, and comprehending when and how ecosystems are affected is an important goal of defaunation ecology. Despite considerable investigation, our understanding is incomplete. Previous research is biased towards the study of seed dispersal in the Neotropics. This study examined whether and how defaunation affects stem density, species diversity, species composition, spatial distribution, and dispersal mode composition of young understorey plants in an Afrotropical setting. Rectangular plots along transects and wedge-shaped plots under focal trees of five mammal-dispersed species were used to compare three sites representing a defaunation gradient in the Dja faunal reserve in Cameroon. Results showed no change in stem density. Woody plant diversity was highest in the most defaunated site, and compositional differences were noted. Under focal trees, the overall abundance of both seedlings and juveniles was similar. The most defaunated site had the highest number of seedlings far from parent trees. More juvenile stems occurred near parent trees in the least defaunated site. This surprising trend might result from fruit dispersal by small, surviving animals and humans more easily collecting fruits, for food or medicinal purposes, in defaunated, more accessible sites. Negligible or no differences in the abundance of animal-dispersed species and other dispersal modes emerged. This study highlights the roles of extant taxa as surrogate providers of ecological services in defaunated Afrotropical forests. Hence, functional compensation is a serious possibility. Additionally, conceptual models of defaunation consequences that exclude the role of humans may not reflect real-world situations. Overall, these investigations suggest that tropical forests, especially those where ecological niches are less partitioned, may be more resilient to defaunation pressures than is often assumed. Effectively conserving extant, and perhaps less iconic, animal species provides hope for defaunated forests.